2017
DOI: 10.5755/j01.ms.23.2.16216
|View full text |Cite
|
Sign up to set email alerts
|

Doped Graphene as Non-Metallic Catalyst for Fuel Cells

Abstract: Aiming a commercial development of proton exchange membrane fuel cells (PEMFC), a low cost, sustainable and high performance electrocatalyst for oxygen reduction reaction (ORR) with capability to replace/reduce rare metals, are high desirable. In this paper, we present a class of doped graphene, namely iodinated graphene with highly ORR electrochemical performances, synthesized by using the electrophilic substitution method. The prepared samples were characterized by different techniques, including Scanning El… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Textural properties of Pt/rGO and Au/rGO. system based on doped graphene can be easily anticipated, taking into account our recent results [11]. This improvement in performance was explained on the basis of higher electrical conductivity and durability parameters, essential for the PEMFC commercialization.…”
Section: Elementmentioning
confidence: 77%
See 2 more Smart Citations
“…Textural properties of Pt/rGO and Au/rGO. system based on doped graphene can be easily anticipated, taking into account our recent results [11]. This improvement in performance was explained on the basis of higher electrical conductivity and durability parameters, essential for the PEMFC commercialization.…”
Section: Elementmentioning
confidence: 77%
“…H 2 SO 4 , KMnO 4 , HI were purchased from Sigma-Aldrich, H 2 O 2 and HCl were obtained from Oltchim SA Romania. The electrocatalysts were synthesized via a facile process ( Figure 1) described in detail elsewhere [11,12]. Graphite oxide was prepared by the oxidation of graphite powder using P 2 O 5 , H 2 SO 4 , and KMnO 4 according to the Hummers' method, namely the graphitic powder was mixed with an oxidizing agent, filtered, washed and dried.…”
Section: Synthesis Of Graphene: Noble Metals Nanocompositesmentioning
confidence: 99%
See 1 more Smart Citation
“…The material has been prepared using AlI 3 catalyst. [ 30 ] Jeon et al reported high‐quality iodine‐doped graphene nanoplatelets by ball milling for 48 h and further freeze drying for 48 h. [ 31 ] Yao et al prepared iodine‐doped graphene‐900 via the facile thermal annealing (at 500–1100 °C) process, which showed decent electrochemical properties. [ 21 ] Luo et al developed nitrogen‐doped graphitic carbon using DES.…”
Section: Introductionmentioning
confidence: 99%
“…However, metal-based electrocatalysts often suffer from some drawbacks, particularly low acidity in the acid medium specific for PEMFC environment. Doping with non-metallic heteroatom is one of the most studied nanocatalysts for the ORR reaction in PEMFC because ized bonds to promote the transfer of the burden due to its large atomic size (the largest in the halogen group) [31][32][33][34][35]. In addition, it is known that the sides of the halogenated graphite have sufficient possibilities to attract O 2 and to weaken the O─O bond from the adsorbed oxygen, thus facilitating efficient conversion into water after reduction and protonation.…”
Section: Introductionmentioning
confidence: 99%